Novel cases of Tunisian patients with mutations in the gene encoding 17β-hydroxysteroid dehydrogenase type 3 and a founder effect. Issue 165 (January 2017) - Ben Rhouma, Bochra; Kallabi, Fakhri; Mahfoudh, Nadia; Ben Mahmoud, Afif; Engeli, Roger T.; Kamoun, Hassen; Keskes, Leila; Odermatt, Alex; Belguith, Neila
Highlights: We describe novel mutations in the HSD17B3 gene causing 46, XY DSD in the Tunisian population. We show that carriers of the p.C206X mutation harbor the same haplotype and provide evidence that the mutation was inherited from a common ancestor. We found a carrier frequency of approximately 1 in 40 in randomly selected individuals from the region of Sfax, Tunisia. This mutation should be considered in the diagnosis and genetic counseling of affected 17β-HSD3 deficiency pedigrees in Tunisia. Abstract: 17β-Hydroxysteroid dehydrogenase type 3 (17β-HSD3) is expressed almost exclusively in the testis and converts Δ4-androstene-3, 17-dione to testosterone. Mutations in the HSD17B3 gene causing 17β-HSD3 deficiency are responsible for a rare recessive form of 46, XY Disorders of Sex Development (46, XY DSD). We report novel cases of Tunisian patients with 17β-HSD3 deficiency due to previously reported mutations, i.e. p.C206X and p.G133R, as well as a case with the novel compound heterozygous mutations p.C206X and p.Q176P. Moreover, the previously reported polymorphism p.G289S was identified in a heterozygous state in combination with a novel non-coding variant c.54G > T, also in a heterozygous state, in a male patient presenting with micropenis and low testosterone levels. The identification of four different mutations in a cohort of eight patients confirms the generally observed genetic heterogeneity of 17β-HSD3 deficiency. Nevertheless, analysis of DNA from 272 randomly selected healthy controls from the same geographic area (region of Sfax) revealed a high carrier frequency for the p.C206X mutation of approximately 1 in 40. Genotype reconstruction of the affected pedigree members revealed that all p.C206X mutation carriers harbored the same haplotype, indicating inheritance of the mutation from a common ancestor. Thus, the identification of a founder effect and the elevated carrier frequency of the p.C206X mutation emphasize the importance to consider this mutation in the diagnosis and genetic counseling of affected 17β-HSD3 deficiency pedigrees in Tunisia.